Volatile sulphur compounds elimination: A new insight in periodontal treatment - Ernie Maduratna Setiawatie; Rikko Hudyono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Recent evidences had demonstrated a link between halitosis and apoptosis in periodontitis. Periodontal pathogenic micro-organisms produce volatile sulphur compounds (VSCs). VSCs are toxic to periodontal tissue. Purpose: The purpose of this paper was to reveal the mechanism of VSCs in periodontal breakdown according to the most recent knowledges. Reviews: Halitosis is mainly attributed to VSCs such as hydrogen sulfide, methyl mercaptan and dimethyl sulfide. Several studies demonstrated a strong relationship between VSCs and periodontal disease progression. VSCs are released from amino acid breakdown from food, protein, cells, blood and saliva. In prone subjects, the VSCs may cause alteration in tissue integrity by increasing its permeability and facilitate the endotoxin to penetrate the tissue barrier. They may also causing apoptotic in gingival and periodontal tissue, which are considered the main pathogenesis in aggravating the periodontitis. VSCs may also initiate the increase of proinflammatory cytokines which is considered to have negative effects in host response. Conclusion: VSCs had been shown to have detrimental effects in gingival and periodontal ligament cells. The use of chlorine dioxine agent and topical antioxidant is beneficial in controlling the periodontal disease severity.Latar belakang: Penelitian terakhir menunjukkan adanya hubungan antara halitosis dengan terjadinya apoptosis pada periodontitis. Mikroorganisme penyebab periodontitis memproduksi volatile sulphur compounds (VSCs) yang bersifat toksik terhadap jaringan periodontal. Tujuan: Tujuan penulisan ini adalah membahas mekanisme VSCs dalam menyebabkan kerusakan periodontal berdasarkan penelitian terakhir yang ada. Tinjauan pustaka: Halitosis seringkali dikaitkan dengan timbulnya VSCs seperti hidrogen sulfida, metil merkaptan, dan dimetil sulfida. Penelitian terakhir menunjukkan bahwa VSCs yang dilepaskan dari pemecahan asam amino makanan ternyata memiliki korelasi dengan kerusakan jaringan periodontal. Pada subjek yang peka, VSCs dapat menyebabkan terjadinya disintegritas epitel dengan meningkatkan permeabilitasnya sehingga endotoksin dapat masuk melewati epitel. Adanya VSCs tersebut memicu terjadinya apoptosis pada jaringan gingiva dan ligamen periodontal, dimana proses ini menyebabkan keparahan penyakit periodontal. VSCs juga dapat mencetuskan peningkatan sitokin proinflamasi yang dapat menyebabkan kerusakan jaringan periodontal. Kesimpulan: VSCs dapat menyebabkan kerusakan pada gingiva dan ligamen periodontal. Penggunaan bahan chlorine dioxine untuk dan antioksidan topikal sangat berguna dalam mengontrol keparahan penyakit periodontal.